Rocket production using organo-mineral fertilizers as a phosphorus source and plant growth-promoting bacteria - Martins, Alexia Amiluana Sousa; Silva, Patrícia Costa; Barbosa, Karine Feliciano; Delmond, Josué Gomes; Ferreira, Ana Flávia Alves; Araújo, Emanuelly Silva; Brasil, Eliana Paula Fernandes; Costa, Adriana Rodolfo da (Food Science and Technology, 2025)
The use of organo-mineral fertilizers in vegetable crops is a promising technology for nutrient supply, particularly when combined with the inoculation of plant growth-promoting bacteria. The objective of this study was to evaluate the biometric parameters and physicochemical quality of rocket crops under the application of organo-mineral fertilizers as a phosphorus source, combined with the inoculation of growth-promoting bacteria. A greenhouse experiment was conducted using a randomized block design with four replications, in a 5 × 2 factorial arrangement consisting of five organo-mineral fertilizer rates (45, 90, 135, 180, and 225 kg ha−1 of P2O5), either with or without inoculation with plant growth-promoting bacteria. The optimal rate of coffee ground-based organo-mineral fertilizers to enhance production and achieve the highest shoot fresh weight in rocket plants was 176.73 kg ha−1 of P2O5. The effect of growth-promoting bacteria on rocket crops was significant for root system development, leading to greater growth. Rocket plants exhibited the highest physicochemical quality in terms of titratable acidity when grown under an organo-mineral fertilizer rate of 154 kg ha−1 of P2O5; however, lower rates are recommended to enhance soluble solids content and pH.